FROM THE HISTORY OF TEXTILE AND SEWING IN THE FERGHANA VALLEY (American Journal of Interdisciplinary Research and Development, 2023)
Given article has been analyzed the history of the textile and sewing in the Ferghana Valley in detail with the help of scientific literature and media as well.